2019
DOI: 10.3389/fimmu.2018.03074
|View full text |Cite
|
Sign up to set email alerts
|

Innate Immunity Provides Biomarkers of Health for Teleosts Exposed to Nanoparticles

Abstract: In recent years, the unique properties of nanoparticles have fostered novel applications in various fields such as biology, pharmaceuticals, agriculture, and others. Unfortunately, their rapid integration into daily life has also led to environmental concerns due to uncontrolled release of nanoparticles into the aquatic environment. Despite increasing awareness of nanoparticle bioaccumulation in the aquatic environment, much remains to be learned about their impact on aquatic organisms and how to best monitor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 182 publications
(233 reference statements)
0
14
0
Order By: Relevance
“…This module was enriched with five GO BP terms and five KEGG pathways, all of which were related to the innate immune system and especially to complement activation (Table S6). Links between exposure to endocrine-disrupting chemicals (EDCs) and modulation of the innate immune system in teleost fish have been established by many previous studies, 57,58 including several that observed the perturbation of pathways related to complement activation with whole-transcriptome profiling. 57,59−61 One review found that parameters related to complement activation showed significant responses 95% of the time (n = 19 exposures) for EDCs and 67% of the time (n = 144 exposures) for all exposures.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This module was enriched with five GO BP terms and five KEGG pathways, all of which were related to the innate immune system and especially to complement activation (Table S6). Links between exposure to endocrine-disrupting chemicals (EDCs) and modulation of the innate immune system in teleost fish have been established by many previous studies, 57,58 including several that observed the perturbation of pathways related to complement activation with whole-transcriptome profiling. 57,59−61 One review found that parameters related to complement activation showed significant responses 95% of the time (n = 19 exposures) for EDCs and 67% of the time (n = 144 exposures) for all exposures.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Hawkins et al, [61] monitored the amount of mucus production and recorded an increase in mucus production in Pimephales promelas gills after 4 h exposure to silver nitrate NPs (AgNO 3 ) that persisted until 24 h. Then, on the third day, the amount of mucous production showed a remarkable decrease. The third study displayed the significant impact of NPs on several innate immune parameters, displaying profound alterations in skin mucus, the function of leukocytes (macrophages and neutrophils), NPs internalization, expression of cytokine, and lysozyme level [58].…”
Section: Discussionmentioning
confidence: 96%
“…Several literature data have addressed the ZnO-NPs toxicity following waterborne exposure to various aquatic organisms [55][56][57]. The innate immune parameters including mucus analysis of the fish skin, leukocytes function, NPs internalization, cytokine expression, and lysozyme level are promising biomarkers to assess fish health upon exposure to NPs [58].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has recently been suggested that haematological, serum biochemical and innate immune parameters are important indicators of health status ( Ahmed & Sheikh, 2019;Fazio, 2019;Fazio et al, 2019;Torrealba et al, 2019). The measurement of blood variables is one of the analytical means in monitoring pathological and physiological changes in relation to nutritional deficiencies, disease, quality of water parameters and environmental monitoring…”
Section: Introductionmentioning
confidence: 99%